2004
DOI: 10.1172/jci200422374
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of protective antibodies are determined by the viral surface antigen

Abstract: Delayed and weak virus neutralizing antibody (nAb) responses represent a hallmark correlating not only with the establishment of persistent infection but also with unsuccessful vaccine development. Using a reverse genetic approach, we evaluated possible underlying mechanisms in 2 widely studied viral infection models. Swapping the glycoproteins (GPs) of lymphocytic choriomeningitis virus (LCMV, naturally persisting, noncytolytic, inefficient nAb inducer) and vesicular stomatitis virus (VSV, nonpersisting, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 39 publications
(28 reference statements)
4
64
0
Order By: Relevance
“…Similar observations of low antivector immunity have been reported for a replication-defective LCMV vector (14) and a replication-competent vesicular stomatitis virus pseudotyped with the LCMV GPC (VSV-GP) (35). The lack of vector-neutralizing antibodies in VSV-GP-immunized mice is a feature attributed to LCMV GPC, since it has been shown that LCMV GPC, and not the vector, determines the kinetics of neutralizing antibody development (36). Our data with the rP18tri vector suggest that PICV GPC may have characteristics similar to those of the LCMV GPC in terms of being a poor inducer of neutralizing antibodies.…”
Section: Discussionsupporting
confidence: 69%
“…Similar observations of low antivector immunity have been reported for a replication-defective LCMV vector (14) and a replication-competent vesicular stomatitis virus pseudotyped with the LCMV GPC (VSV-GP) (35). The lack of vector-neutralizing antibodies in VSV-GP-immunized mice is a feature attributed to LCMV GPC, since it has been shown that LCMV GPC, and not the vector, determines the kinetics of neutralizing antibody development (36). Our data with the rP18tri vector suggest that PICV GPC may have characteristics similar to those of the LCMV GPC in terms of being a poor inducer of neutralizing antibodies.…”
Section: Discussionsupporting
confidence: 69%
“…5), antibodies to LCMV have a limited capacity to prevent reinfection 6,8 , a property that could have explained the superior performance of rLCMV-OVA in homologous prime-boost immunizations (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…LCMV-induced T cell responses are broad and long-lived 7 , and LCMV infection has been widely studied as a model of CTL-mediated protection. The neutralizing antibody response to LCMV is extraordinarily weak, and convalescent serum fails to prevent re-infection 6,8 . These characteristics suggested that modified LCMV might serve as a vector for the induction of CTL immunity.…”
mentioning
confidence: 99%
“…Although the absence of an initial robust nAb response has been primarily attributed to antiviral escape mechanisms (32, 48), the immunological processes that drive the disruption of humoral immunity during persistent infection are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%